Healthy Parent Carers programme: development and feasibility of a novel group-based health-promotion intervention - Borek, A; Mcdonald, B; Fredlund, M; Bjornstad, G; Logan, S; Morris, C (BioMed Central, 2018)
Background Parent carers of disabled children report poor physical health and mental wellbeing. They experience high levels of stress and barriers to engagement in health-related behaviours and with ‘standard’ preventive programmes (e.g. weight loss programmes). Interventions promoting strategies to improve health and wellbeing of parent carers are needed, tailored to their specific needs and circumstances. Methods We developed a group-based health promotion intervention for parent carers by following six steps of the established Intervention Mapping approach. Parent carers co-created the intervention programme and were involved in all stages of the development and testing. We conducted a study of the intervention with a group of parent carers to examine the feasibility and acceptability. Standardised questionnaires were used to assess health and wellbeing pre and post-intervention and at 2 month follow up. Participants provided feedback after each session and took part in a focus group after the end of the programme. Results The group-based Healthy Parent Carers programme was developed to improve health and wellbeing through engagement with eight achievable behaviours (CLANGERS – Connect, Learn, be Active, take Notice, Give, Eat well, Relax, Sleep), and by promoting empowerment and resilience. The manualised intervention was delivered by two peer facilitators to a group of seven parent carers. Feedback from participants and facilitators was strongly positive. The study was not powered or designed to test effectiveness but changes in measures of participants’ wellbeing and depression were in a positive direction both at the end of the intervention and 2 months later which suggest that there may be a potential to achieve benefit. Conclusions The Healthy Parent Carers programme appears feasible and acceptable. It was valued by, and was perceived to have benefited participants. The results will underpin future refinement of the intervention and plans for evaluation.